P131 Impact of Inflammatory Bowel Disease on patients' caregivers: Results from a French cohort. (21st January 2022) - El Hajj MD, W; Buisson, A; Olympie, A; Ravel, M H; Devos, C; Trang, C; Nahon, S
Abstract: Background: Inflammatory Bowel Disease (IBD) has an important impact on patients' quality of life (QOL). Data on its impact on patients' close relatives are limited. This study aims at exploring the effect of IBD on patients' caregivers (PC). Methods: We have conducted an online survey about the impact of IBD on PCs via the social network of the French association of IBD patients (Association François Aupetit) between october 16th and november 23rd 2020. The burden the disease had on their psychological, professional and social life was evaluated through a computerized questionnaire. Results: Eight hundred and fifty-three PCs aged > 16 years were interrogated. 77% were females. Their relatives had Crohn's disease (CD) in 63% and Ulcerative colitis (UC) in 35% of cases. Patient was the child in 57% or the partner in 31% of cases. Fifty four percent of PCs had never heard about IBD before the diagnosis of their relatives, and upon disease announcement, 86% experienced a feeling of worry, sadness or anxiety. They were regularly searching informations about the disease through internet websites, IBD associations or health care professionals in 72, 68 and 53% of cases, respectively. Main concerns included novel therapies (55%), treatment side effects (45%), long term disease consequences (52%) and dietary limitations (47%). Twenty percent considered that they were still not well informed about the disease. The most significant impact on daily PCs' life was psychological as they were regularly experiencing anxiety and incapacity in 94% of cases. Concerning professional impact, 36% of PCs needed to reduce or to adjust their work time, to work from home or even to change or leave their work. Among partners, the disease impacted their sexual life as 22% reported a decrease in their desire/libido and 14% reported an absence of sexual relation for weeks or months. Sixty four percent have waived many social activities as going out with friends, holidays or cinema. More than 50% wished they had more psychological support as well as more information about the disease and the way they could help their relatives. The main factors associated with a higher psychological impact were the following: Female sex (OR 2.23; 95%CI 1.51–3.28; p<0.0001), parental status (OR 2.29; 95%CI 1.28–4.11; P<0.0001), IBD duration <5 years (OR 1.72; 95%CI 1.11–2.66; P=0.005) and the lack of information about the disease (OR 0.59; 95%CI 0.39–0.88; P=0.01). Conclusion: IBD had an important impact on PCs' QOL at personal and social levels. A psychological support and an appropriate information about the disease and the help they can provide to their relatives are essential to reduce the burden of IBD on their daily life.